SUSTAINABLE FINANCE FROM THE PERSPECTIVE OF MAQASHID SYARIAH - Anisa, Lina Nur (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2025)
Sustainable finance has become a global concern as the need for a more inclusive and socially and environmentally responsible economic system increases. In the context of Islamic finance, the principles of maqashid syariah provide a strong normative foundation for developing sustainable finance concepts based on ethics, justice, and balance. This study aims to analyze how maqashid syariah can serve as a foundation for implementing sustainable finance by examining Islamic financial instruments such as green sukuk, productive waqf, as well as mudharabah and musyarakah schemes. The method used in this research is library research with a qualitative approach, where data is collected from various academic sources such as books, journals, and research reports related to Islamic finance and sustainability. The study’s findings indicate that the principles of maqashid syariah align with the objectives of sustainable finance, particularly in economic justice, equitable wealth distribution, and socially and environmentally responsible investments. The implementation of Islamic financial instruments supporting sustainable development has been observed in several countries, such as Malaysia and the United Arab Emirates, which have adopted Environmental, Social, and Governance (ESG)-based regulations. However, challenges such as a lack of Islamic financial literacy, regulatory limitations, and insufficient innovation in financial instruments remain major obstacles to implementing sustainable Islamic finance. Therefore, this study recommends strengthening policies, improving Islamic financial literacy, and fostering innovation in syariah-compliant financial instruments to enhance the integration of maqashid syariah into the sustainable finance system. Keywords: sustainable finance, perspective, maqashid syariah